Curative and Preventive Roles of Catholic Missionaries in Kihanja and Ihangiro Bukoba District from 1904-1961 - Kaiza, Jason C.; Kapinga, Osmund M (International Journal of Humanities and Education Development (IJHED), 2020)
This paper identifies the curative and preventive roles of Catholic missionaries in the development of health services in Kihanja and Ihangiro chiefdoms in Tanzania from 1904 to 1961. The study is based on historical design and qualitative approach. The documentary, in-depth interviews and observation methods were employed in data collection. In disagreeing to traditional scholars, the paper advocates that missionaries did not only offer curative health services but also provided a variety of preventive services mainly in rural areas where up to the 1930s government hospitals and dispensaries were either very few or non-existent. The curative services provided by Catholic missionaries consisted of surgical and non-surgical treatments as well as nursing care activities. The preventive roles included Maternal and Child Health (MCH), health education, training of midwives, vaccination, and leprosy and tuberculosis services. The paper emphasizes that missionary health services not only complemented government’s services in the colony but also pioneered medical provision in the rural areas where the colonial state lacked resource to invest. Missions’ efforts to collaborate with the government was not made to perpetuate colonialism but rather to facilitate the availability of more health services.